Ultra‐Stable and Robust Response to X‐Rays in 2D Layered Perovskite Micro‐Crystalline Films Directly Deposited on Flexible Substrate. Issue 1 (24th October 2021) - Lédée, Ferdinand; Ciavatti, Andrea; Verdi, Matteo; Basiricò, Laura; Fraboni, Beatrice
Abstract: 2D layered hybrid perovskites have recently attracted an increasing interest as active layers in LEDs and UV–Vis photodetectors. 2D perovskites crystallize in a natural self‐assembled quantum well‐like structure and possess several interesting features among which low‐temperature (<100 °C) synthesis and low defect density. Here are presented solid‐state ionizing radiation direct detectors based on the 2D layered hybrid perovskite PEA2 PbBr4 (PEA = C6 H5 C2 H4 NH3 + ) deposited from solution using scalable techniques and directly integrated onto a pre‐patterned flexible substrate in the form of micro‐crystalline films displaying crystal‐like behavior, as evidenced by the ultra‐fast (sub‐microsecond) and good detection performances under UV light. The effective detection of X‐rays (up to 150 kVp) is demonstrated with sensitivity values up to 806 µC Gy −1 cm −2 and Limit of Detection of 42 nGy s −1, thus combining the excellent performance for two relevant figures of merit for solid‐state detectors. Additionally, the tested devices exhibit exceptionally stable response under constant irradiation and bias, assessing the material robustness and the intimate electrical contact with the electrodes. PEA2 PbBr4 micro‐crystalline films directly grown on flexible pre‐patterned substrate open the way for large‐area solid‐state detectors working at low radiation flux for ultra‐fast X‐ray imaging and dosimetry. Abstract : Here are presented solid‐state ionizing radiation direct detectors based on micro‐crystalline 2D layered hybrid perovskites films processed at low temperature. They show sub‐microsecond and stable response, X‐rays sensitivity of 806 µC Gy −1 cm −2, Detection Limit of 42 nGy s −1 . PEA2 PbBr4 films directly grown on flexible pre‐patterned substrate open the way for large‐area detectors working at low radiation flux for ultra‐fast X‐ray imaging and dosimetry.